Trajectories of adolescent psychopathology among youth who were maltreated and placed in out-of-home care. (June 2022) - Hong, Kajung; Morelli, Nicholas M.; Garcia, Jackelyne; Duong, Jacqueline B.; Evans, Meghan C.; Litrownik, Alan J.; Villodas, Miguel T.
Abstract: Background: Although researchers have found an increased risk for psychopathology among maltreated adolescents placed in out-of-home care, different trajectories of psychopathology by out-of-home placements have not been previously studied. Objective: The current study is built on previous investigation of youth in different long-term out-of-home placements and examined the trajectories of adolescent psychopathology by out-of-home placement classes. Participants and setting: We leveraged data from the Southwestern site of the Longitudinal Studies of Child Abuse and Neglect. Participants included caregiver-youth dyads ( N = 273), who had substantiated reports of child maltreatment (CM) prior to children's age four and were placed in out-of-home care. Methods: Five out-of-home placement classes from ages 4 to 12 (i.e., stable adopted, stable reunified, stable kinship care, stable non-kin foster care, and unstable placement) were identified from previous study and participants were interviewed at youth ages 12, 14, and 16 to assess adolescent psychopathology. Latent Growth Curve Analysis was used to examine trajectories of psychopathology by placement classes. Results: Adolescents in unstable placement and stable adopted classes had higher intercepts and more positive or less negative slopes for psychopathology compared to those in stable kinship care and stable reunified classes. Conclusions: Adolescents in unstable placement and stable adopted classes were at similarly elevated risk for psychopathology, whereas adolescents in stable kinship care and stable reunified classes were at lower risk for psychopathology. We discuss the clinical implication to preventing and intervening risks for psychopathology among maltreated youth in unstable and adopted placements.